Pemodelan Sistem Legasi Kepada Sistem Berasaskan Web Menggunakan UML - Abd. Rasid, Mamat (2002)
This project is aiming at producing standard process model for re-engineering legacy software to web based. This process model is produced from callobarating software re-engineering process model and database by J-I Hainaut and J Henrard and WebE model. With the existence of this model, it can be reference for an organization who want to develop web based software from existing software. This can be cost saving. This model is develop using Unified Modeling Language (UML). One prototype has been develop for this project using this model. In the last section, discussion of strenghts and weaknesses of this model and the required steps which are need to be done to further strengten the produced model.